PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBANTUAN EDPUZZLE KEPADA SISWA KELAS IV GUGUS V KECAMATAN GEROKGAK - Made Dendi Aditya Putra; I Made Sedana; IG Agung Jaya Suryawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop interactive multimedia assisted by Edpuzzle for fourth-grade elementary school students in the IPAS subject on the topic